2017
DOI: 10.1371/journal.pone.0188607
|View full text |Cite
|
Sign up to set email alerts
|

Investigating endogenous µ-opioid receptors in human keratinocytes as pharmacological targets using novel fluorescent ligand

Abstract: Opioids in skin function during stress response, regeneration, ageing and, particularly in regulating sensation. In chronic pruritus, topical treatment with Naltrexone changes μ-opioid receptor (μ-OR) localization to relieve itch. The molecular mechanisms behind the effects of Naltrexone on μ-OR function in reduction of itching behavior has not been studied. There is an immediate need to understand the endogenous complexity of μ-OR dynamics in normal and pathological skin conditions. Here we evaluate real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
3
4
0
2
Order By: Relevance
“…The release of inflammatory factors, notably IL-1β, induces the expression and release of opioids by these cells, which, once attached to the receptors of peripheral nerve fibers, inhibit neuronal triggering and transmitter release [12][13][14][15][16] . The present study demonstrated that supernatant from keratinocyte and fibroblast culture promotes analgesia during inflammatory pain induced by carrageenan in a model of mechanical hyperalgesia, corroborating previous studies [16][17][18][32][33][34] . The data obtained suggest that the opioid receptor seems to be involved in the analgesic effect of keratinocyte culture.…”
Section: Discussionsupporting
confidence: 92%
“…The release of inflammatory factors, notably IL-1β, induces the expression and release of opioids by these cells, which, once attached to the receptors of peripheral nerve fibers, inhibit neuronal triggering and transmitter release [12][13][14][15][16] . The present study demonstrated that supernatant from keratinocyte and fibroblast culture promotes analgesia during inflammatory pain induced by carrageenan in a model of mechanical hyperalgesia, corroborating previous studies [16][17][18][32][33][34] . The data obtained suggest that the opioid receptor seems to be involved in the analgesic effect of keratinocyte culture.…”
Section: Discussionsupporting
confidence: 92%
“…The release of inflammatory factors, notably IL-1β, induces the expression and release of opioids by these cells, which, once attached to the receptors of peripheral nerve fibers, inhibit neuronal triggering and transmitter release [12][13][14][15][16] . The present study demonstrated that supernatant from keratinocyte and fibroblast culture promotes analgesia during inflammatory pain induced by carrageenan in a model of mechanical hyperalgesia, corroborating previous studies [16][17][18][32][33][34] . The data obtained suggest that the opioid receptor seems to be involved in the analgesic effect of keratinocyte culture.…”
Section: Discussionsupporting
confidence: 92%
“…34 The finding that both FBNTI and MDAN-21 display 100 nM range antinociception via topical administration is of particular significance in light of evidence for the presence of multiple opioid receptors (MOR, DOR, and KOR) in the skin. 35,36,27,28,37,38 Given our recent finding 3 that loperamide and oxymorphindole synergize in the central terminals of nociceptive afferents, it is likely that FBNTI and MDAN-21 are acting at the peripheral terminals of these afferents after topical application. Notably, a recent report 39 has described the presence of a subepidermal meshlike network of two sensorreceptor cell types that influence the sensation of pain.…”
Section: ■ Discussionmentioning
confidence: 99%